A meta-analysis of copper level and risk of preeclampsia: evidence from 12 publications. Issue 4 (24th August 2016) - Fan, Yuqin; Kang, Yan; Zhang, Min
Abstract : The association between copper level and risk of preeclampsia (PE) has produced inconsistent results. Thus, a meta-analysis was conducted to summarize the evidence from epidemiological studies for copper level and PE risk. Pertinent studies were identified by a search of PubMed and Web of Knowledge up to April 2016. Standardized mean difference (SMD) was performed to combine the results. Random-effect model (REM) was used. Publication bias was estimated using Egger's regression asymmetry test. Twelve articles (10 case–control studies and 2 cross-sectional studies) involving 442 PE cases and 463 health controls were included in this meta-analysis. Our pooled results suggested that PE patients had a higher copper level compared with healthy pregnancy controls [summary SMD=0.69, 95% CI: 0.54–0.84, I 2 =96.7%; P <0.001]. The association was also significant in Asian population [SMD=0.73, 95% CI=0.57–0.90, I 2 =97.3%] and European populations [SMD=0.50, 95% CI=0.14–0.86, I 2 =58.9%]. After conducting the subgroup analysis and sensitive analysis, the results showed consistent significant association with the one based on all studies. No publication biases were found. Our analysis indicated that plasma or serum copper level in PE patients was significantly higher than that in healthy pregnancy women.